Prognostic and Clinical Value of Sirt1 Expression in Gastric Cancer：A Systematic Meta-Analysis - 姜斌 陈锦皇 袁文正 纪金童 刘正义 吴亮 唐强 舒晓刚 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Many studies have reported that the expression of silent information regulator 1（Sirt1） is associated with the clinical features and prognosis of patients with gastric cancer, but the exact function remains controversial. We conducted this study to illustrate the clinical and prognostic value of Sirt1 in gastric cancer. The related publications before December 2015 were searched in the databases including Pubmed, Cochrane Library, Embase and China National Knowledge Infrastructure（CNKI）. The studies were included and excluded according to the inclusion criteria and exclusion criteria. The 3- and 5-year overall survival（OS） and clinical features such as age, T stage, N stage and differentiation were analyzed by software Rev Man 5.3. A total of 1650 patients in 7 studies were included according to the inclusion criteria and exclusion criteria. The high expression of Sirt1 was found in 58.4% cases by immunohistochemistry. High expression of Sirt1 was closely linked with the 3-year OS（OR=0.25, 95% CI： 0.16–0.39, P0.00001, fixed）, patient＇s age（≥60 years old vs. 〈60 years old; OR=1.43, 95% CI： 1.06–1.93, P=0.02, fixed）, T stage（T3＋T4 vs. T1＋T2; OR=1.45, 95% CI： 1.08–1.94, P=0.01, fixed）, N stage（N1＋N2＋N3 vs. N0; OR=3.47, 95% CI： 2.39–5.05, P〈0.00001, fixed） and tumor differentiation（G1＋G2 vs. G3; OR=0.50, 95% CI： 0.35–0.69, P〈0.0001, fixed）. Nevertheless, it seemed that high expression of Sirt1 was not associated with 5-year OS（OR=0.44, 95% CI： 0.15–1.28, P=0.13, random）. It was suggested that the high expression of Sirt1 implies a poor prognosis of gastric cancer patients in a relatively short period（3 years）, but not in a long time（≥5 years）. The expression of Sirt1 is also linked with patients＇ age, T stage, N stage and tumor differentiation.